Fisheries Management Interventions in Lake Nasser; Improving fish production and food security in Upper Egypt - Aly, Walid (2018)
As part of the IFPRI Egypt Seminar in partnership with WorldFish: “Leveraging Aquaculture and Fisheries for Improving Food and Nutrition Security in Egypt”